METHODS OF TEACHING ECONOMIC TERMINOLOGY TO STUDENTS OF ECONOMICS BASED ON THE CVI (CONTENT AND VOCABULARY INTEGRATED) APPROACH - Zairova Madina (TADQIQOTLAR, 2025)
Abstract:  This  article  explores  effective  methods  of  teaching  economic terminology  to  students  of  economics  through  the  CVI  (Content  and  Vocabulary Integrated)  approach,  which  emphasizes  the  simultaneous  development  of  subject knowledge  and  professional  vocabulary.  The  study  highlights  how  integrating economic  content  with  targeted  vocabulary  instruction  enhances  learners’ comprehension,  retention,  and  practical  use  of  specialized  terms.  Drawing  on contemporary  pedagogical  theories  and  classroom  practices,  the  article  examines strategies  such  as  contextualized  reading,  task-based  learning,  case  studies, collaborative  activities,  and  authentic  materials  related  to  economic  discourse.  The findings suggest that the CVI approach promotes deeper conceptual understanding, supports communicative competence in professional contexts, and increases students’ motivation by linking language learning directly to their academic field. The study underscores the value of integrated instruction for preparing economics students to operate effectively in academic and real-world economic environments.